Tesla Coil-Based Wireless Power Transfer: Design, Performance, and Future Directions - Kulkarni, Swati; Batod, Swastik; Singh, Suraj Kumar; Saini, Tejas; Vanshaj, Vanshaj (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2026)
Tesla coil-based wireless power transfer (WPT) has attracted increasing attention because of its ability to transmit electrical energy without physical connections through high-frequency resonant coupling. However, existing studies remain fragmented across power electronics, high-voltage engineering, education, and electric vehicle applications, with limited integrated evaluation of design, performance, safety, and implementation challenges. This review synthesizes the literature on Tesla coil-based WPT published between 2016 and 2024, together with selected foundational studies, to examine design principles, performance characteristics, application domains, safety considerations, and remaining research gaps. The synthesis indicates that system performance is governed by the interaction of four key parameters: coupling coefficient, quality factor, resonant frequency, and mutual inductance. Existing studies demonstrate reliable short-range power transmission and substantial voltage amplification, but also highlight strong electromagnetic fields that require standardized safety assessment before practical deployment. Tesla coil-based WPT is particularly suitable for educational demonstrations, laboratory prototypes, and other low-power applications because of its simplicity and low cost. In contrast, its loose-coupling architecture limits efficiency and scalability for high-power applications, including electric vehicle charging, when compared with conventional inductive WPT systems. Future research should establish standardized safety protocols, perform quantitative comparisons between spark-gap and solid-state Tesla coil configurations, and validate renewable-energy-integrated WPT systems under realistic operating conditions.